Crisis and Literature: Future Imperfect, or the Case of Don DeLillo’s Cosmopolis - Sári B., László (FOCUS: Papers in English Literary and Cultural Studies, 2018)
In his afterword to The Cambridge Companion to Don DeLillo (2008), Joseph M. Comte makes a strong case for positioning the author as a writer of historical liminality, and citing DeLillo himself, he claims that Cosmopolis is a text “poised liminally ‘between the end of the Cold War and the beginning of the Age of Terror’” (183). Not yet aware of the shift taking place in the author’s interest from all matters historical to his previous preoccupation with corporeality and writing, Comte goes on to argue that DeLillo’s novel of 2003 stages how “[c]yber-capital and terrorism contend within the singularity of global power” (185), inasmuch as the text is preoccupied with what commentators usually identify as “the technological sublime” (186) in DeLillo’s oeuvre, in this case representing the “interaction between technology and capital, the inseparability” of the two (23). Comte and other scholarly commentators praise Cosmopolis exactly for what it was criticized for at the time of its publication, its witty handling of academically embedded ideas, thereby somewhat downplaying how the text, as I will argue, discusses, or indeed embodies, some of these ideas in relation to the white male body and terrorism in a curious temporal structure: written after 9/11, but presenting what one may call reverse déjà vu of the terror attacks. Comte’s estimation is, therefore, in line with the contemporary reviews of the book at the time of its publication, and stresses the intellectual achievement and poetic qualities of the text.